Pembangunan dan penilaian bahan pengajaran dan pembelajaran berasaskan web – Webquest bagi mata pelajaran ICT - Norazah Mohd. Nordin,; Ngau, Chai Hong (penerbit ukm, 2009)
In the era of globalization, educators should give more attention on the innovations of information delivery methods to students. This article discusses the development process of a web-based teaching courseware, WebQuest, for the Form Four ICT subject. The article also discusses the evaluation of the interface and the content of the WebQuest. The development methodology includes the phases of analysis, design, development, inplementation and evaluation. For the evaluation phase, a set of survey form is used to evaluate the interface and the teaching and learning structure of the content. The samples are twenty one students from two schools who are taking ICT subject. The outcome of the research reveals that the overall presentation of the WebQuest entitled Computer System: System Concept is relevent and successful in attracting the students’ interest towards the topic.